PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX MTsN LEMBAH GUMANTI - Atul Usna, Imra; Rahmi, Rahmi; febriana, Rina (STKIP PGRI Sumbar, 2014)
Â ABSTRACTThis research is motivated by the students mathematical understanding concepts which are still low and less active in learning process. This research aims to determine whether students mathematical understanding concepts by implementing cooperative learning model type Team Assisted Individualization (TAI) better than the students mathematical understanding concepts by implementing conventional learning and find out how the development of students learning activity progess by implementing cooperative learning model type Team Assisted Individualization (TAI). This kind of this research is experimental. The sampling technique is random sampling. The instrument used is the observation of student activity sheets and final test students understanding of mathematical concepts. Form of the test used is the reliability essay 0,741. The results obtained from testing the hypothesis P-value = 0.013 is less than a = 0.05 then the hypothesis is accepted. It can be concluded that the students mathematical understanding concepts by implementing cooperative learning model type Team Assisted Individualization (TAI) is better than the students mathematical understanding concepts by implementing conventional learning class IX students MTsN Lembah Gumanti.Â